Sub-chronic toxicity of the active fraction of a modified Huang-Lian-Jie-Du Decoction - Lan Wang; Wen Yang; Jia-Qian Zhu; Yan-feng Huang; Mei Zhong; Steven King Fan Loo; Siu Po Ip; Yan-Fang Xian; Zhi-Xiu Lin (Toxicology Reports)
A traditional Chinese herbal medicine formula named Huang-Lian-Jie-Du Decoction (HLJDD) has been used to cure various inflammatory diseases with a long history. However, one component of HLJDD Gardeniae fructus has remarkable liver and kidney toxicities. Therefore, it was altered with Dictamni cortex to form a modified HLJDD (MHLJDD). In this study, we aimed to evaluate the sub-chronic toxicity of the active fraction of MHLJDD (MHLJDD-F) in rats. Adult rats of both sexes were intragastrically administered with vehicle or MHLJDD-F (at the dose of 170, 340, and 680 mg/kg/day) once daily for 90 days. Half of the rats from each group were kept for an additional 30-day period to observe the drug withdrawal effect. The signs of toxicity and mortality of the rats were observed, and the body weight and food consumption were recorded. Blood was collected for hematological and biochemical analyses and major organs were weighed and harvested for histopathological examinations. The results revealed that no systemic toxicity of MHLJDD-F was found during the experiments. Organ coefficients and pathological alterations of major organs were comparable to the control rats. The no-observed adverse effect level (NOAEL) of MHLJDD-F was found up to 680 mg/kg/day. All these results demonstrated that long-term oral administration of MHLJDD-F did not cause significant toxicity, which is worthy to be widely applied as a new herbal medicine in pre-clinical and clinical studies.